Turkey's Improving Integration with the Global Capital Market Impacts on Risk Premia and Capital Costs - Gönenç, Rauf (OECD Economics Department Working Papers, 2010)
Turkey has considerably improved its terms of access to the global capital market. Progress in macroeconomic fundamentals has enhanced credibility and reduced risk premia and capital costs. This has had broad effects on capital supply conditions in the entire economy. Real interest rates have declined, and funds of lengthened maturity are becoming available for a broader range of borrowers and fund users, offering a basis for broader-based long-term growth. Estimations in the paper suggest that reinforcing fiscal institutions, price stability, governance quality, political stability and trade and growth performance would help Turkey to continue to improve its integration with the international capital market and reduce durably its capital costs. This paper relates to the 2010 OECD Economic Review of Turkey (www.oecd.org/eco/surveys/turkey)